2006
DOI: 10.1111/j.1365-2249.2006.03009.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclass distribution of natural salivary IgA antibodies against pneumococcal capsular polysaccharide of type 14 and pneumococcal surface adhesin A (PsaA) in children

Abstract: SummaryA number of studies have shown that the ratio of IgA1 and IgA2 subclasses in secretions can depend upon the nature of the antigen inducing their production. In order to evaluate the effect of the nature of the antigen on the subclass distribution of the naturally occurring salivary IgA antibodies against Streptococcus pneumoniae , we used enzyme immunoassay to measure the levels of natural IgA, IgA1 and IgA2 antibodies to pneumococcal capsular polysaccharide type 14 (PS14) and pneumococcal surface adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…While IgA1 responds to protein and polysaccharide antigens, IgA2 seems to specialize in polysaccharide antigens. 86,87 Despite its lack of FcgR interaction, IgA possesses significant effector functions that occur through binding to FcaRI on various leukocytes. While binding to macrophages and neutrophils elicits phagocytosis, neutrophils and eosinophils release cytotoxic granules in an ADCC mechanism similar to that of IgG-ligated NK cells.…”
Section: Immunoglobulin Amentioning
confidence: 99%
“…While IgA1 responds to protein and polysaccharide antigens, IgA2 seems to specialize in polysaccharide antigens. 86,87 Despite its lack of FcgR interaction, IgA possesses significant effector functions that occur through binding to FcaRI on various leukocytes. While binding to macrophages and neutrophils elicits phagocytosis, neutrophils and eosinophils release cytotoxic granules in an ADCC mechanism similar to that of IgG-ligated NK cells.…”
Section: Immunoglobulin Amentioning
confidence: 99%
“…Further investigation as to whether loss of diversity in the B cell repertoire correlated with poor vaccine responses against influenza and pneumonia indicated that it may be a contributory factor, but that other factors were likely also involved (Ademokun et al, 2011 ). These two vaccines generate different responses; influenza is believed to mainly induce IgG1/IgG3/IgA1 T-dependent responses (Brown et al, 1985 ; Hocart et al, 1990 ; Powers, 1994 ), while pneumococcal responses are thought to be T-independent and can lead to significant elevation of IgA2/IgG2 antibodies in the serum and mucosa (Lue et al, 1988 ; Carson et al, 1995 ; Sanal et al, 1999 ; Simell et al, 2006 ; Benckert et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The innate B cell response is based on the specificity of the antibody (germline-encoded antibody specificities), the faster kinetics of antibody generation by some B cell subsets and memory in the form of a preformed, perhaps somewhat static repertoire. Subsets of B cells (B-1 and marginal zone) based on expression of a skewed antibody specificity are part of the innate immune B cell system, and in some cases were clearly shown to produce highly protective natural antibodies (IgA) against Streptococcus pneumonia (211). Using transgenic mice Haas and co-workers demonstrated that B1a B cells are necessary for natural antibody that reduced the susceptibility to infection while B1b cells produced protective anti-pneumococcal polysaccharide antibody (93).…”
Section: Receptor Specificity Of Innate and Adaptive B Cellsmentioning
confidence: 99%